PERANAN PEMBELAJARAN ORGANISASIONAL DALAM MENGKONVERSIKAN ORIENTASI PASAR MENJADI KINERJA PEMASARAN : PROSES DAN AGENDA PENELITIAN - SULIYANTO SULIYANTO (Universitas Islam Nahdlatul Ulama Jepara, 2010)
ABSTRACT Many studies have proved that market orientation has an influence on marketing performance, but it is considered a market orientation is not sufficient to improve marketing performance. Market orientation will be able to improve marketing peribrmahce when combined with organizational learning, but the role of organizational learning in the convert market orientation into marketing performance is unclear. By integrating variables of organizational learning as a single entity-market orientation organizational learning- innovation, competitive advantage marketing performance in a study as one is expected to darify the role of /earning in the convert market orientation into marketing performance has been deemed not dear. Key Word: OrganizationatLearning, Market Orientation, Competitive advantage and Marketi